Establishing the Evaluation Criteria System for Private Security Companies in Hungary - Tóth, Attila (Magyar Rendészet, 2023)
The study was prepared for the research on the creation of the certification system for private security companies operating in Hungary. I hereby present the place of private security in the Hungarian law enforcement system and examine the operation of the certification system for private security companies in international practice. Based on international experience and taking into account laws applicable to businesses, I have developed a criteria system for the pre-certification of businesses. I have also created separate evaluation criteria systems for assessing the financial stability, size, market share and quality of services provided by companies.